Some results for the almost and weakly star Lindelof - Lakehal Rachid; Seba Djamila (University Of Eloued جامعة الوادي, 2020)
We discuss some of the selected results obtained in the past fteen years on the principles of star selection in topology, which is an important sub- eld in the eld of theory of selection principles. The main theory of selections mainly describes. overlap properties and local properties in topological spaces. we nd that they are used in many domains, including probability games ........... So in this paper we introduce and study some new types of star-selection principles: almost star Lindelof and weakly star Lindelof and we give some properties of these selection principles are proved.
Intervention
Keywords: Selection principles; star Rothberger; star Lindelof; star-Menger space; almost; weakly